CHANGE IN THE IMAGE OF REGION TOWARD THE SPATIAL SETTING AND BEHAVIOR (A case study of Tamansari "Cyber" Village, Yogyakarta) - Bhanu Rizfa Hakim; Amos Setiadi (DIMENSI (Journal of Architecture and Built Environment), 2021)
Cyber village is a residential area in RT (neighborhood association) 36 in the tourist area in Tamansari Yogyakarta. It has recognized image as an information technology based region with good internet network. Internet technology at the cyber village is slowly changing the behavior of the citizens from the social, economy, culture and tourism aspects. The behavior changes on the social, economic, cultural and tourism aspects affect the spatial setting at Tamansari "cyber" village to become a unique tourist area. The methods used in this research were Qualitative Research through observation to identify phenomena that occur, interviews, and literature studies that were analyzed by behavior setting method. The results of this research showed that changes in the image of the region influence the citizens’ behavior that finally creates certain spatial settings to meet the needs for space which could accommodate the village potentials, covering the social, economic, tourism and cultural potentials.